2021
DOI: 10.1097/eja.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moderate intraoperative blood loss and norepinephrine therapy on sublingual microcirculatory perfusion in patients having open radical prostatectomy

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These contradictory observations may, in part, result from using different camera technologies and analysis methods. Further, studies reporting preserved FCD found either increased 20 or decreased 19 microvascular blood flow. In our study, preserved tRBCp and FCD indicate that microcirculatory tissue perfusion was not impaired under general anaesthesia before surgical incision -despite reduced microcirculatory flow (RBCv and PPV) and clinically important decreases in blood pressure and cardiac output.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These contradictory observations may, in part, result from using different camera technologies and analysis methods. Further, studies reporting preserved FCD found either increased 20 or decreased 19 microvascular blood flow. In our study, preserved tRBCp and FCD indicate that microcirculatory tissue perfusion was not impaired under general anaesthesia before surgical incision -despite reduced microcirculatory flow (RBCv and PPV) and clinically important decreases in blood pressure and cardiac output.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies investigating the effects of general anaesthesia on sublingual microcirculatory tissue perfusion showed inconsistent results. Some studies found reduced 18,21 and others preserved 19,20 FCD under general anaesthesia compared with pre-induction baseline. These contradictory observations may, in part, result from using different camera technologies and analysis methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations